Narrative Analysis and the Transformation of Exegetical Methodology: A Systematic Literature Review of Methodological Approaches and Interpretive Frameworks (2000-2025) - Mohammad Rindu Fajar Islamy; Asep Abdul Muhyi; Achmad Faqihuddin (Universitas Islam Negeri Sunan Kalijaga, 2026)
The application of narrative analysis to Quranic interpretation (tafsir) has emerged as a significant methodological approach in contemporary Islamic scholarship, bridging classical exegetical traditions with modern literary theory. This systematic literature review examines the development of narrative analysis methodology as a formal analytical framework for interpreting the Qur’an between 2000 and 2025. In this study, tafsir is no longer treated as the primary methodological framework; rather, it is positioned as historical and textual data that can be analyzed using modern narratological tools. The analysis reveals three dominant approaches in treating tafsir texts as material objects: structural analysis, intertextual analysis, and contextual analysis. Following PRISMA guidelines, we conducted a comprehensive search across multiple academic databases, identifying 191 relevant studies. The review identifies significant methodological innovations, including the integration of digital humanities tools, comparative narrative approaches, and cross-cultural interpretive frameworks. Key findings indicate that narrative analysis in tafsir has evolved from descriptive storytelling approaches to sophisticated hermeneutical methodologies that engage with both classical Islamic exegetical traditions and contemporary literary theory. The study reveals gaps in comparative cross-cultural narrative analysis and limited integration of cognitive narrative theory. This review contributes to the understanding of contemporary tafsir methodology and provides a foundation for future research in narrative-based Quranic interpretation.